Passive stereoscopy for control of industrial robots - Sung, Eric. (2008)
The project is focused on stereovision for robotic applications. To achieve the aims of robotic applications, the stereovision system is meant to derive 3-D information from a set of cameras (minimum of two). In our case, three cameras were used to enable disambiguation of homologous image point matching. The matching was automated by the implementation of the minimum distance measure algorithm proposed and tested by the author.